Stigmatisation and resistance processes: Reflections on the field of HIV research and an agenda for contemporary stigma studies - Laio Magno; Veriano Terto; Richard Parker (Taylor & Francis Group, 2024)
Stigmatisation processes constitute key barriers to effectively addressing the HIV pandemic. In this article, we provide a critical overview of this field's current state of the art, highlighting some key emerging issues that merit greater research attention in the future to ensure that contemporary research on stigmatisation and resistance processes continues to engage with changing social and political circumstances. We look at how resistance to stigma has developed in the context of HIV and highlight some of the most important programmatic strategies that have emerged over the history of the pandemic. We present the key concepts of 'moral panics' and 'necropolitics', and we articulate them in relation to new global phenomena that deepen the processes of stigmatisation. Moreover, we identify an agenda for investigation which merits greater attention in future research, intervention, and advocacy: 1) changing political environments, neoliberalism, growing political polarisation, and the rise of political extremism; 2) the rise of the information age, technological change, and social media; and 3) rebuilding civil society and governmental responses to stigma.